Girls$1 (Btennis :s conquering the court - Rusch, Elizabeth (Mankato, Minn. : Capstone Press, 2007)
"Describes tennis, the skills needed for it, and ways to compete"--Provided by publisher.
Includes bibliographical references (p. 31) and index
Includes bibliographical references and index.
Keywords: Tennis for girls -- Juvenile literature